Literature Study Analysis of Indonesian Entrepreneurs' Attitudes in Doing Business - Elisa Betty Manullang; Primus Paroloan Simarmata (Universitas Negeri Medan, 2023)
Entrepreneurship is a person's attitude and ability to handle a business or other activity in an effort to find, create, apply technology, work methods and production with improvements in providing better services in order to obtain large profits. Entrepreneurship is a process of innovation and creativity that has a high risk in producing products that can provide benefits to society and can prosper entrepreneurs. Entrepreneurship is the right solution for economic problems such as unemployment and poverty in Indonesia, because armed with only a diploma and less entrepreneurial skills so that many people queue for jobs. While the number of entrepreneurs in Indonesia is still recorded at 0.43% of the total productive age population, this figure is very far behind neighboring countries, such as Singapore where the number of entrepreneurs has reached 7%, Malaysia 5%, and Thailand 3%. Meanwhile, according to the chairman of KPPU said that in 2017 the number of entrepreneurs in Indonesia ranged from 1.6%-1.8% of the total population in Indonesia. This number is still very far from the standards of developed countries with a minimum number of entrepreneurs of 2% of the total productive age, to overcome this the government seeks to create 20,000 new entrepreneurs and the development of 1,200 Small and medium industry centers or can be called SMIs. In this article, I provide an idea of analyzing the attitude of Indonesian entrepreneurs in doing business. The method used in this article is to study the literature and review some of the references obtained. Thus, it is hoped that this idea will have a good impact on readers and provide changes for Indonesian entrepreneurs in the future. So that entrepreneurs know how the attitude they must highlight in doing business.